2019
DOI: 10.12688/f1000research.16817.2
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota profiling with long amplicons using Nanopore sequencing: full-length 16S rRNA gene and the 16S-ITS-23S of the rrn operon

Abstract: Background: Profiling the microbiome of low-biomass samples is challenging for metagenomics since these samples are prone to contain DNA from other sources (e.g. host or environment). The usual approach is sequencing short regions of the 16S rRNA gene, which fails to assign taxonomy to genus and species level. To achieve an increased taxonomic resolution, we aim to develop long-amplicon PCR-based approaches using Nanopore sequencing. We assessed two different genetic markers: the full-length 16S rRNA (~1,500 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 53 publications
3
74
0
Order By: Relevance
“…Emerging singlemolecule (third-generation/long-read) sequencing technologies including Pacific Biosciences ("PacBio") and Oxford Nanopore Technologies ("nanopore") produce reads 10s to 100s of kilobases in length, often without prior amplification. Recent work [14][15][16][17] has demonstrated the utility of these longer reads for sequencing the entire 16S gene or entire rRNA operon, with corresponding increase in taxonomic resolution by capturing more variable sequence, including all nine variable regions of 16S, the internal transcribed spacers (ITS), and 23S. To support the extension of these approaches to characterize strain-level variation of tissue-associated (mucosaassociated) microbiota contributing to IBD and in models of experimental colitis in mice, with a particular focus on mechanistic studies of AIEC, we produced complete genome assemblies for eight AIEC and non-AIEC E. coli, describe the genomic variation among these strains, particularly within the rRNA operon, and demonstrate the accurate identification of these strains in mixed in vitro and in vivo microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging singlemolecule (third-generation/long-read) sequencing technologies including Pacific Biosciences ("PacBio") and Oxford Nanopore Technologies ("nanopore") produce reads 10s to 100s of kilobases in length, often without prior amplification. Recent work [14][15][16][17] has demonstrated the utility of these longer reads for sequencing the entire 16S gene or entire rRNA operon, with corresponding increase in taxonomic resolution by capturing more variable sequence, including all nine variable regions of 16S, the internal transcribed spacers (ITS), and 23S. To support the extension of these approaches to characterize strain-level variation of tissue-associated (mucosaassociated) microbiota contributing to IBD and in models of experimental colitis in mice, with a particular focus on mechanistic studies of AIEC, we produced complete genome assemblies for eight AIEC and non-AIEC E. coli, describe the genomic variation among these strains, particularly within the rRNA operon, and demonstrate the accurate identification of these strains in mixed in vitro and in vivo microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…These results were consistent with observations from [ 61 ], which showed that the bacterial identification at the genus level was reliable. Species-level missclassifications could be partially addressed by employing different—and optimized—bioinformatic approaches for the taxonomic classification [ 45 , 62 ], by sequencing the complete 16S-ITS-23S region of the ribosomal operon [ 63 , 64 ], or by coupling MinION sequencing with complementary quantitative PCR assays [ 60 ].…”
Section: Supporting Microbiome-driven Industrial Processesmentioning
confidence: 99%
“…The long reads generated can allow taxonomic classification with greater specificity than is possible with short reads. 4 Additionally, as reads containing antimicrobial resistance determinants (with the exception of those on plasmids) contain greater amounts of genetic context than is found with short reads, assignment of resistance determinants to a species is more precise. However, ONT data contains a substantial per base error rate of up to 10% with assemblies containing open reading frame disrupting insertion or deletion errors.…”
Section: Introductionmentioning
confidence: 99%